Learning To Read More Fun: Loose Parts Approach For Children Aged 5–6 Years At Bukit Permai 2 Kindergarten - Riskal Fitri; Endang Endang; Nurhafsah Nurhafsah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2026)
This community service aims to deeply describe how the loose parts approach can be utilized to support early reading skills in 5–6 year old children at TK Bukit Permai 2. The concept of loose parts refers to various detached objects that do not have a fixed shape or function, such as bottle caps, stones, popsicle sticks, or colorful buttons, which allow children to manipulate, combine, and create according to their imagination. This approach is believed to stimulate creativity, exploration, and early literacy skills in a fun way and in accordance with the developmental stages of early childhood. The method used in this service is descriptive qualitative and classroom action research (CAR) with data collection techniques through direct observation of children's activities in the classroom and visual documentation during the process. The results of the service show that the application of loose parts in reading learning is able to create a more active, interactive, and meaningful learning atmosphere. Children become more enthusiastic in recognizing letters, distinguishing initial sounds, and arranging syllables or simple words through structured free play. In addition, this approach also encourages social involvement, communication, and self-confidence of children during the learning process.